Exploring youth vaping in New Zealand intermediate and high schools: a mixed-methods study protocol - Jagroop-Dearing A; Lañas–Pangan J; Khan MH; Dearing CG; Forrest RH (BioMed Central Limited, part of Springer Nature, London, 2025)
Background: Electronic nicotine delivery systems (ENDS) represent a global growing public-health concern among adolescents. In Aotearoa New Zealand (NZ), daily vaping rates have risen sharply (10.5%) among 15–17-year-olds in 2023/24. This is alarming due to nicotine’s addictive nature and its impact on adolescent brain development, mental health, and academic performance. Māori youth and those in socio-economically deprived areas are disproportionately affected, exacerbating existing health-inequities. Legislative frameworks prohibit vaping on school premises, yet ease of access remains a concern. Punitive school responses are increasingly viewed as harmful and ineffective, highlighting an urgent need for evidence-based, health-centred interventions. Methods: This multiphase, mixed-methods study explores vaping within secondary schools on the East Coast, NZ. Phase 1 involves online surveys to collect quantitative data on vaping behaviours, targeting 1375 students to ensure sufficient statistical power. Initial qualitative data will be gathered alongside. Phase 2 employs in-depth interviews and focus groups with students (vapers/non-vapers) and staff to explore perceptions of health risks, access, and effectiveness of school responses. A rapid scoping review (RSR) will synthesise existing research on adolescent vaping in Oceanic countries, identifying behavioural patterns, legislative impacts, and gaps in the evidence base. Discussion: This protocol addresses critical knowledge gaps by integrating quantitative and qualitative findings with a RSR. This study aims to inform the development of culturally appropriate, health-based, vape prevention and cessation strategies. Ultimately, findings may support a paradigm shift away from punitive disciplinary measures towards supportive school-based interventions, that improve public-health outcomes and reduce health inequities.
Keywords: Youth-vaping; Health-equity; New Zealand; Schools; Mixed-methods; Public-health